English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

a. f^-1(x)=7x-2
b. f^-1(x)=1/2x+7
c. f^-1(x)=x+7 /2
d. f^-1(x)=x +7/2

2007-01-29 11:25:08 · 4 answers · asked by lana l 1 in Science & Mathematics Mathematics

4 answers

let f(x) = y

y = 2x - 7

y + 7 = 2x

(y + 7) / 2 = x

Now we got an equation for 'x' in terms of 'y'. By definition, the inverse of f(x) in none other than 'x' itself. So,

f^-1(x) = x = (y + 7) / 2

Hence, choice (c)

2007-01-29 11:32:52 · answer #1 · answered by Anonymous · 0 0

y=2x-7

exchangle x and y
x=2y-7
2y= x+7
y= 1/2x+7/2

f^-1(x)= 1/2x+7/2

2007-01-29 19:32:40 · answer #2 · answered by      7 · 0 0

first, you have to rewrite the equation to y=2x-7
Then, switch x and y, so x=2y-7
Then solve for y...so once you add 7, you have 2y=x+7
After dividing by 2, you get (x+7)/2
the answer is c

2007-01-29 19:32:31 · answer #3 · answered by Mr. Irrelevant 3 · 0 0

-2x-7

2007-01-29 19:45:06 · answer #4 · answered by ema 3 · 0 0

fedest.com, questions and answers